Semiconductor materials in analytical applications of surface‐enhanced Raman scattering. (8th December 2015) - Ji, Wei; Zhao, Bing; Ozaki, Yukihiro
Abstract : Surface‐enhanced Raman scattering (SERS) is increasingly becoming an important analytical technique in various fields, which can mostly be attributed to the significant evolution of SERS‐active substrates. The semiconductor‐based SERS technique is particularly interesting because the inherent physicochemical properties of semiconductor materials offer several possibilities for the development and improvement of SERS‐based analytical techniques. According to the effect of the semiconductor materials in SERS, semiconductor‐based SERS techniques can be categorized into two areas: (1) semiconductor‐enhanced Raman scattering, in which a semiconductor material is directly used as a substrate for enhancing Raman signals of adsorbed molecules, and (2) semiconductor‐mediated‐enhanced Raman scattering, in which a semiconductor is employed as an 'antenna' or 'trap' to modulate the Raman enhancement originating from a metal substrate. While the theory on semiconductor‐based SERS is still incomplete and evolving, semiconductor‐based SERS techniques have already resulted in substantial progress in biological analysis, photocatalysis, solar cells, sensing, and optoelectronic devices. The aim of this review is to outline the recent progress in this emerging research field, with a special emphasis on its analytical performance and application areas. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The inherent physicochemical properties of semiconductor materials offer several possibilities for the development of novel SERS‐based analytical techniques. This review was aimed to provide a succinct overview on the exciting applications of semiconductor materials in SERS‐based experiments.